Implemented PWIM in Developing Students’ Communicative Competence of SMK Islam Wijaya Kusuma Jakarta - Siti Nurani; Amrina Rosyada (Lingua Cultura, 2017)
The research aimed at determining the significant effect of implemented Picture Word Inductive Model (PWIM) in developing students’ communicative competence in SMK Islam Wijaya Kusuma Jakarta. The students’ communicative competence was measured quantitatively by conducting the experiment method. There were 47 of the eleventh-grade students as samples chosen randomly by using purposive sampling technique. The data were performed by using the test instrument with two groups on post-test design; one group became the experiment class and the other group became the control class. The questionnaire was assigned to students at the end of the lesson. The post-poster cycle assessment was given as a basis of measurement in analyzing students’ communicative competence. The data were analyzed by using t-test two tailed formula to find out the significant difference of each class of the sample (simple effect). Findings have shown that there is a significant effect of using PWIM to students’ communicative competence which is reflected from the enhancement of students’ comprehension toward the pronunciation, fluency, grammar, vocabulary as well as the increase of their motivation and creativity experiencing thelearning process more communicatively.